2021
DOI: 10.1161/jaha.121.021542
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic Dynamic Contrast‐Enhanced Magnetic Resonance Lymphangiography: Potential Imaging Signature for Protein‐Losing Enteropathy in Congenital Heart Disease

Abstract: Background Protein‐losing enteropathy (PLE) is a significant cause of morbidity and mortality in congenital heart disease patients with single ventricle physiology. Intrahepatic dynamic contrast‐enhanced magnetic resonance lymphangiography (IH‐DCMRL) is a novel diagnostic technique that may be useful in characterizing pathologic abdominal lymphatic flow in the congenital heart disease population and in diagnosing PLE. The objective of this study was to characterize differences in IH‐DCMRL findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Protein losing enteropathy is the most common lymphatic flow disorder in the abdomen and affects 5%-12% (40, 41) of Fontan patients. Intrahepathic and intramesenteric dynamic contrast magnetic resonance lymphangiography recently demonstrated abnormal increased lymphatic flow from the liver lymphatics (Figures 4A,B) or to a lesser extend from the mesenterial lymphatics (Figures 4C,D) to the duodenum in these patients (42,43). Duodenal wall edema, inflammation and lymphangiectasia is commonly seen on endoscopy and even holes formed in the duodenal wall have been demonstrated in later stages in these patients (25).…”
Section: Lymphatic Flow Disorders In Single Ventricle Patientsmentioning
confidence: 84%
See 1 more Smart Citation
“…Protein losing enteropathy is the most common lymphatic flow disorder in the abdomen and affects 5%-12% (40, 41) of Fontan patients. Intrahepathic and intramesenteric dynamic contrast magnetic resonance lymphangiography recently demonstrated abnormal increased lymphatic flow from the liver lymphatics (Figures 4A,B) or to a lesser extend from the mesenterial lymphatics (Figures 4C,D) to the duodenum in these patients (42,43). Duodenal wall edema, inflammation and lymphangiectasia is commonly seen on endoscopy and even holes formed in the duodenal wall have been demonstrated in later stages in these patients (25).…”
Section: Lymphatic Flow Disorders In Single Ventricle Patientsmentioning
confidence: 84%
“…The three main access points are intranodal for the central lymphatics, intrahepatic for hepato-systemic lymphatics and intramesenteric whose role is not well-defined yet. It can even be done in very small infants that weight approximately 3 kg (Figures 4A-E) (42,49,50). In patients where multiple compartments are involved all three access points can be investigated at the same time.…”
Section: Dynamic Contrast-enhanced Magnetic Resonance Lymphangiographymentioning
confidence: 99%
“…However, not all patients with a Fontan circulation develop severe lymphatic abnormalities and it is hypothesized that the physiologic changes in venous and lymphatic congestion, plus an anatomical variant of the lymphatic vasculature, might lead to lymphatic failure in some of those patients [ 14 ]. This would explain why some patients with high CVP do not develop lymphatic failure and some who seem to have favorable hemodynamics might show severe lymphatic dysfunction [ 2 , 3 , 15 , 16 ]. In our cohort, we did not identify any correlation between ventricular dysfunction or hemodynamic parameters with lymphatic classification.…”
Section: Discussionmentioning
confidence: 99%
“…T2-weighted imaging has become increasingly important for single-ventricle patients and represents a ‘game changer’ to screen patients with Fontan failure, including PLE and plastic bronchitis. However, new modalities have been described to illustrate the lymphatic perfusion, including nodal, hepatic and mesenteric dynamic contrast lymphangiography (DCMRL) [ 11 , 16 , 18 ]. DCMRL allows for a full characterization of lymphatic perfusion, including physiology, anatomy, and flow of the lymphatic system.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent manuscript, Smith et al showed the correlation between the different hepatic lymphatic flow patterns and systemic lymphatic diseases (16). In addition, Lemley et al demonstrated that all patients with PLE have duodenal involvement with IH-DCMRL (17). In contrast, most patients without PLE do not have duodenal involvement with hepatic injection.…”
Section: Lymphatic Imagingmentioning
confidence: 99%